Livestock production in central Mali: The Macina wool sheep of the Niger inundation zone - Wilson, R.T. (Springer, 1983)
Outlines the supposed origins, known history and distribution of Macina sheep in the Niger innundation zone of Mali w. a physical description of the breed, discussing population demography and traditional systems of management; evaluates productivity using results of a questionnaire survey of traditional owners and analysis of four years' data on a small flock owned by ILCA and managed on traditional lines.